Antitumor immunotherapeutic and toxic properties of an HDL-conjugated chimeric IL-15 fusion protein - Ochoa, María C. (2013)
Interleukin (IL)-15 effects on CD8 T and natural killer (NK) lymphocytes hold promise to treat cancer. Fusion proteins have been engineered to provide IL-15 receptor alpha (IL-15Rα) mediated trans-presentation to lymphocytes and extend the plasma half-life of the cytokine. In this study, we report on a triple fusion protein combining apolipoprotein A-I (Apo A-I), IL-15, and IL-15Rα's sushi domain. Apo A-I conveys IL-15 to high-density lipoproteins (HDL), from which the cytokine is trans-presented by the IL-15Rα's sushi domain. Such a construction was tested by hydrodynamic gene transfer to the liver of mice. Lethal toxicity was observed upon injection of 10 μg of the expression plasmid. Mice died from an acute lymphocytic pneumonitis in which T and NK cells dominate a severe inflammatory infiltrate. Importantly, mice devoid of NK cells were not susceptible to such toxicity and mice lacking granzymes A and B also survived the otherwise lethal gene transfer. Lower plasmid doses (<2.5 μg) were tolerated and dramatically increased the numbers of NK and memory CD8 T lymphocytes in the liver, spleen, and lungs, to the point of rescuing the deficiency of such lymphocyte subsets in IL-15Rα−/− mice. Doses of plasmid within the therapeutic window successfully treated metastatic tumor models, including B16OVA lung metastasis of melanoma and MC38 colon cancer liver metastasis. Sushi-IL-15-Apo as a recombinant protein was also bioactive in vivo, became conjugated to HDL, and displayed immunotherapeutic effects against metastatic disease.